1988
DOI: 10.1007/bf00153701
|View full text |Cite
|
Sign up to set email alerts
|

Retinal toxicity of antibiotics: Evaluation by electroretinogram

Abstract: Toxicity of an intravitreal injection of gentamicin sulfate, disodium sulbenicillin and cefazolin sodium on the retina was investigated by electroretinogram in albino and pigmented rabbits. Recordings were made before injection and 2 hours and 3, 7, 14, and 21 days after injection. Significant differences were found in the susceptibility of the electroretinogram components to various antibiotics as follows. Gentamicin 0.24 mg/0.1 ml irreversibly abolished all the components examined. Sulbenicillin 4.0, 8.0, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…Nevertheless, an intravenous treatment with enrofloxacin prior to vitrectomy did not alter the cultivation of leptospires from vitreal samples significantly (Popp et al 2013). Besides the influence of gentamicin on cultivation attempts, its retinal toxicity needs to be considered (D'amico et al 1984, Hancock et al 2005, Mochizuki et al 1988. Not only the gentamicin-concentration, but also the ocular pigmentation and the manner of application can influence the toxic effects of gentamicin on the retina (Peyman et al 1974, Zemel et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an intravenous treatment with enrofloxacin prior to vitrectomy did not alter the cultivation of leptospires from vitreal samples significantly (Popp et al 2013). Besides the influence of gentamicin on cultivation attempts, its retinal toxicity needs to be considered (D'amico et al 1984, Hancock et al 2005, Mochizuki et al 1988. Not only the gentamicin-concentration, but also the ocular pigmentation and the manner of application can influence the toxic effects of gentamicin on the retina (Peyman et al 1974, Zemel et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a reference to intravitreal cefazolin causing a short-term selective suppression of oscillatory potentials on electroretinogram, it has been shown to be safe and nontoxic in rabbit models. 25,26 Lastly, economic considerations for widespread adoption of a dropless protocol for the 3 million cataract surgeries performed each year were explored in a 2015 report by Cataract Surgeons for Improved Eyecare (CSIE), which suggested that Medicare could save $7.1 billion, while patients could cut $1.4 billion in out-of-pocket costs between 2016 and 2025. 27 In 2006, there were an estimated 225,000 pars plana vitrectomies performed in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal damage can lead to vision loss due to lack of transmission of visual signal and has been in the top 5 most important causes of new drug candidate dismissal during drug development process (50). Dark-adapted ERG was used as a non-invasive in vivo evaluation of the electrical response of retinal cells.…”
Section: Electroretinographymentioning
confidence: 99%
“…The same lack of significant difference was observed when comparing ERG results of tests groups versus control group 7 days after IVT administration. This results are of great importance because we are challenging a new formulation of a drug that has been previously proved as safe for intravitreal injection by many other independent research groups, but also, this same drug has also been found to be toxic to the ocular structures when formulated in certain excipients with specific deterioration of retinal function evidenced by unfavorable electroretinography results (50). Interestingly, the b-wave response in the ERG of the group administered with 40 μg of rapamycin was statistically different from control group and of its original basal measurements due to increased amplitude observed in this group after treatment.…”
Section: Electroretinographymentioning
confidence: 99%